2005
DOI: 10.1111/j.0906-7590.2005.04182.x
|View full text |Cite
|
Sign up to set email alerts
|

Abundance patterns and coexistence processes in communities of fleas parasitic on small mammals

Abstract: R. 2005. Abundance patterns and coexistence processes in communities of fleas parasitic on small mammals. Á/ Ecography 28: 453 Á/464.The abundance of a given species in a community is likely to depend on both the total abundance and diversity of other species making up that community. A large number of co-occurring individuals or co-occurring species may decrease the abundance of any given species via diffuse competition; however, indirect interactions among many cooccurring species can have positive effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 71 publications
5
49
0
Order By: Relevance
“…Male-biased parasitism rates, as observed here for mites and M. walkeri, have been recorded in a number of blood-feeding arthropods and may be explained by the effect of testosterone, which is higher in males and is known to depress the immune response to parasites (Harder et al 1994;Hughes & Randolph 2001;Josabel Belliure 2004;Cox & John-Alder 2007). Previous studies have also found correlations in parasite burden between different flea species (Krasnov et al 2005) and between different life stages of ticks (Randolph et al 1999). Such associations may be due to facilitation by the suppression of the immune system (Krasnov et al 2005) or correlated small-scale spatial variation in risk due to microclimatic conditions.…”
Section: Discussionsupporting
confidence: 77%
“…Male-biased parasitism rates, as observed here for mites and M. walkeri, have been recorded in a number of blood-feeding arthropods and may be explained by the effect of testosterone, which is higher in males and is known to depress the immune response to parasites (Harder et al 1994;Hughes & Randolph 2001;Josabel Belliure 2004;Cox & John-Alder 2007). Previous studies have also found correlations in parasite burden between different flea species (Krasnov et al 2005) and between different life stages of ticks (Randolph et al 1999). Such associations may be due to facilitation by the suppression of the immune system (Krasnov et al 2005) or correlated small-scale spatial variation in risk due to microclimatic conditions.…”
Section: Discussionsupporting
confidence: 77%
“…A comparison of the present results with those of Krasnov et al (2005) on the abundance patterns in component communities of Xeas parasitic on small mammals suggests that some rules governing the communities of diVerent parasite taxa within the same host taxon are similar, whereas other rules vary among parasite taxa. For example, the relationships between the mean abundance of a parasite species and the pooled abundances of other co-occurring parasites belonging to the same taxon were predominantly positive in both Xeas and gamasids.…”
Section: Discussionsupporting
confidence: 54%
“…Obviously, characters that make a host species preferred over other host species by a haematophagous parasite could be the same for diVerent taxa of haematophages. These are characters that allow a parasite either to obtain more food or to obtain food of higher quality, or that make food acquisition easier (Kelly and Thompson 2000;Krasnov et al 2005). For example, hosts may diVer in their skin structure which may be extremely important for mite feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Host body size can determine the number of parasites per host, as more space is available for multiple parasite individuals on larger hosts (e.g. Morand and Guégan 2000, but see Krasnov et al 2005a). Host species also diVer in the level of their immune and behavioural defence against parasites (Klein and Nelson 1998;Mooring et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…tabanids) ectoparasites of terrestrial hosts may be much more strongly inXuenced by their oV-host environment than both the endo-or permanent ectoparasites studied by Arneberg et al (1997) and Poulin (2006). For example, survival and abundance of Xeas are strongly aVected by the microclimate of the host's nest/burrow (Krasnov et al 2001(Krasnov et al , 2002b, host identity (Krasnov et al 1998) and the total abundance and diversity of co-occurring Xea species (Krasnov et al 2005a). This suggests that the patterns reported by Arneberg et al (1997) and Poulin (2006) may not be valid for terrestrial arthropod ectoparasites.…”
Section: Introductionmentioning
confidence: 99%